Effect of precipitation on the background levels of the atmospheric β- and γ-radiation; Applied Radiation and Isotopes; Vol. 118 - Yakovleva V. S. Valentina Stanislavovna; Nagorsky P. M. Petr Mikhaylovich; Cherepnev M. S. Maksim Sviatoslavovich; Kondrateva (Kondratieva) A. G. Alla Georgievna; Ryabkina K. Kseniya (2016, 2016)
Title screen